Immunologic Aspects of Perioperative Nutrition - Andersen, L.; Rasmussen, M.; Holgersen, R. Beier (Journal of Nutritional Therapeutics, 2016)
Nutrition has proven to be of great importance for the postoperative clinical outcome. Several studies have shown that infectious complications in the surgical patient , are reduced by pre- or postoperative nourishment. We discuss cellular immunity in relation to both enteral and parenteral nutrition and present an updated literature study of current evidence. The aim of this paper is to give an overview of studies, that compare different immunological parameters in the surgical patient being nourished either enterally or parenterally.